The practical workbook. Content module 1, 2 - Mykhailovska, N. S.; Grytsay, A. V.; Михайловська, Наталія Сергіївна; Грицай, Ганна Володимирівна (Zaporozhye state medical university, 2017)
The practical work book for academic discipline «General practice – family medicine» for content module 1,2 for students of 6th studying year, international faculty is according to the educational program of academic discipline «General practice – family medicine», speciality 7.12010001 «Medicine». The practical work book includes situational tasks, questions, tests for current control, the patient record protocol for general practitioner (was developed by department of General practice – family medicine). Materials appearing in practical work book covered the theoretical knowledge and practical skills for students of 6th studying year international faculty.